Organizational Commitment Mediates Work Leadership And Performance - Ervan Yansen; Nurlaely; Angga Rizka Lidiawan (Faculty of Economics, Merdeka University Surabaya, Indonesia, 2025)
This study aims to analyze the influence of leadership and work environment on employee performance in Correctional Institutions (Prisons), as well as the mediating role of organizational commitment. The research method used is a quantitative approach with Structural Equation Modeling-Partial Least Squares (SEM-PLS) analysis. The results show that leadership does not have a significant effect on employee performance (O = 0.193, T = 1.506, P = 0.133) but has a positive effect on organizational commitment (O = 0.633, T = 9.985, P = 0.000). Organizational commitment does not significantly influence employee performance (O = 0.022, T = 0.162, P = 0.872), while the work environment significantly influences employee performance (O = -0.349, T = 4.107, P = 0.000) but not organizational commitment (O = 0.063, T = 0.718, P = 0.473). Additionally, organizational commitment does not mediate the relationship between leadership and work environment on employee performance (O = 0.014, T = 0.158, P = 0.874; O = 0.001, T = 0.088, P = 0.930). The implications of these findings indicate that improving employee performance in prisons is not sufficient solely by enhancing leadership aspects or organizational commitment; instead, there is a need for a more conducive work environment and more effective managerial strategies. Recommendations for prison management include improving leadership competencies, enhancing workplace facilities, and implementing employee welfare programs. This study is expected to serve as a reference for academics and practitioners in the development of human resource management within correctional institutions.